Imaging high-speed friction at the nanometer scale - Per-Anders Thorén (Nature Portfolio, 2016)
It has been a challenge to characterize microscopic origins of friction at high velocities. Here authors extend atomic force microscopy to develop a dynamic technique combining force sensitivity and spatial resolution and able to probe, at each image pixel, frictional forces at velocities up to several cm per second.